Use of Learning Video Media to Improve Science Learning Outcomes of The Fifth Grade Students - Restijayanti, Restijayanti (Universitas Sebelas Maret, 2020)
The purpose of this study is to improve student learning outcomes in science learning of the fifth grade. This research is a classroom action research (PTK) which is carried out in three cycles, each cycle consists of planning, implementation, observation, and reflection stages. The subject of this study is 11 students of the fifth grade of SDN Guntur in the academic year 2020/2021. Data collection techniques use observation and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the use of learning video media can improve science learning outcomes of the fifth grade students in the academic year 2020/2021 evidenced by the percentage of learning outcomes completeness and class average score. In the first cycle only reaches 72,73 % and the class average score is 72,36, in the second cycle becomes 100 % with the class average score 82,09 and in the third cycle reaches 100 % with the class average score 86,91.